Prospective Analysis of Commercial Relations - López Alcívar, Francisco Javier (Alternativas, 2019)
Although international trade generates benefits over wealth and it also provides access to new and better products, it is considered as one of the causes of inequality in the world, as wealth flows are mostly concentrated in the owners of capital. In this document an analysis of the exchange relations between Ecuador and China is carried out; the evidence shows an open specialization of these nations towards products with little added value and high added value respectively. This productive approach has resulted in a deficit trade balance for Ecuador. The maintenance of this productive structure may mean for Ecuador a stagnation of its national industry because the leap towards a more modern economy is not privileged, but rather a refocusing of the Ecuadorian production is encouraged. This study has a quantitative and descriptive methodological orientation, it uses secondary information collected in the WTO Trade Map tool. The results suggest that, given the asymmetric characteristics of the bilateral relations between Ecuador and China, it is necessary to proceed with the signing of trade agreements, based on the most favored nation terms, where the easy access of Ecuador to China's primary market is protected on the one hand, and on the other hand, the development of economic complementation projects based on the technological transfer that allows the construction of a major basic industry in Ecuador.